A structured RNA motif locks Argonaute2:miR-122 onto the 5’ end of the HCV genome - Luca F. R. Gebert (Nature Portfolio, 2021)
The RNA genome of the Hepatitis C Virus binds to the liver-specific miR122. Here the authors report the crystal structure of the Ago2:miR122:HCV complex showing that the viral RNA’s structural element traps the Ago2:miR-122 complex on the 5’ end of the viral genome to protect it from degradation.